Preschoolers' behavioural reenactment of "failed attempts": The roles of intention-reading, emulation and mimicry - Huang, C; Heyes, C; Charman, T (2006)
To clarify the nature of the social cognitive skills involved in preschoolers' reenactment of actions on objects, we studied 31- and 41-month-old children's reenactment of intended acts ("failed attempts") in Meltzoff's (Meltzoff, A. N. (1995). Understanding the intentions of others: Reenactment of intended acts by 18-month-old children. Developmental Psychology, 31, 838-850) behavioural reenactment paradigm. Measuring children's first action, performance of target acts was similar in a novel Emulation Learning condition to that seen in the Failed Attempt condition. In the Emulation Learning condition, children did not see the adult's manipulation and their response was likely to have been based on the end state specifying the object's key affordances. Both 31- and 41-month-old children also copied the control acts they had observed in the Adult Manipulation condition. However, 41-month-old but not 31-month-old children reproduced the failed attempt actions in the Failed Attempt condition. This pattern of findings suggests that, whilst 2- to 3-year-olds mimic adults' actions when these actions do not trigger alternative object affordances, only in the third year of life will children mimic adults' actions when these actions simultaneously trigger such affordances. Reenactment of actions on objects involves a number of social cognitive processes and exceptional care in the design of experiments is required to determine the roles played by intention-reading, emulation, and mimicry. © 2005 Elsevier Inc. All rights reserved.